Spider-monkey Optimization for the Secure-aware Routing in the Networks - Shijoe Jose, D. Malathi (International Journal of Advanced Science and Technology, 2020)
Now-a-days people all over the world are using the world-wide-web (WWW) for multiple applications, which makes security an important concern. The routing in the network is secured by initiating the identification of the genuine users in the network and by blocking the internet access to the illegitimate users. A secure-aware routing strategy based on the spider-monkey optimization (SMO) algorithm is proposed in this paper. Initially the intruders in the network are detected, and the secure routing is initiated in the network based on the SMO algorithm, which employs a multi-objective constraint. The proposed secure routing in the network enables a trust worthy communication in the network with minimal delay and minimal energy consumption. The performance analysis of the SMO-based secure routing is enabled based on the performance metrics, such as Delay, throughput, and Number of Alive Nodes with respect to various network attacks. The simulation results reveal that the proposed method acquired the minimal delay of 0.060s, maximal alive nodes of 77, and maximal throughput of 99.42% bps when compared with the existing methods.